2018
DOI: 10.1016/j.yjmcc.2017.11.014
|View full text |Cite
|
Sign up to set email alerts
|

HAX-1 regulates SERCA2a oxidation and degradation

Abstract: Ischemia/reperfusion injury is associated with contractile dysfunction and increased cardiomyocyte death. Overexpression of the hematopoietic lineage substrate-1-associated protein X-1 (HAX-1) has been shown to protect from cellular injury but the function of endogenous HAX-1 remains obscure due to early lethality of the knockout mouse. Herein we generated a cardiac-specific and inducible HAX-1 deficient model, which uncovered an unexpected role of HAX-1 in regulation of sarco/endoplasmic reticulum Ca-ATPase (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 56 publications
1
23
0
Order By: Relevance
“…Our finding that PLN ablation increases susceptibility to thermal inactivation of SERCA2a in mouse cardiac tissue is consistent with an increased susceptibility to ischemic cardiac injury in those animals [32]. Furthermore, the cardiac-specific ablation of the anti-apoptotic protein HAX-1, decreases PLN binding to SERCA2a [58] and increases SERCA2a oxidation and degradation and susceptibility to ischemic cardiac injury [59], whereas over-expression of HAX-1 protects against ischemic injury [60].…”
Section: Discussionsupporting
confidence: 81%
“…Our finding that PLN ablation increases susceptibility to thermal inactivation of SERCA2a in mouse cardiac tissue is consistent with an increased susceptibility to ischemic cardiac injury in those animals [32]. Furthermore, the cardiac-specific ablation of the anti-apoptotic protein HAX-1, decreases PLN binding to SERCA2a [58] and increases SERCA2a oxidation and degradation and susceptibility to ischemic cardiac injury [59], whereas over-expression of HAX-1 protects against ischemic injury [60].…”
Section: Discussionsupporting
confidence: 81%
“…Hematopoietic cell-specific protein 1-associated protein X-1 (HAX1) is a multifunctional protein ~35 kda in size and is involved in anti-apoptosis, migration, adhesion and endocytosis regulation (9)(10)(11). A previous study found that highly-expressed HAX1 is associated with poor survival in human colorectal cancer (12), cutaneous squamous cell carcinoma (13), laryngeal carcinoma (14) and multiple myeloma (15).…”
Section: Introductionmentioning
confidence: 99%
“…In the present study, we report that SERCA2a is transcriptionally regulated by YAP, such that reduced levels of YAP cause SERCA2a downregulation in I/R-treated cardiomyocytes. In addition, a recent study has reported that HAX-1 regulates post-transcriptional modifications, including oxidation and degradation, of SERCA2a in cardiomyocytes [ 46 ]. SERCA2a downregulation or inactivation is closely associated with myocardial infarction [ 47 ], atrial arrhythmias [ 48 ], hypertension [ 49 ], cardiac aging [ 50 ], heart failure [ 51 ], and myocardial hypertrophy [ 52 ].…”
Section: Discussionmentioning
confidence: 99%